Leachability of zinc ions from ternary phosphate glasses - Pyare R. (My University, 2025)
With a view to using glasses as a source of zinc, which is one of the micronutrients required by plants, a systematic study on leachability of zinc ions from ternary phosphate glasses having molar composition 60ZnO·5X·35P2O5 (where X = Li2O, Na2O, K2O, CaO, B2O3 and SiO2) was carried out. Leaching of zinc ions has been studied as a function of pH and the results show that leaching increases with increasing pH of the solutions. The concentration of zinc ions in the leachate decreases with increasing bond strength between non-bridging oxygen ions and the cations in glasses. The leaching of zinc ions increases with increase in leaching time and decreases with increase in particle size of glasses. P2O5 was also leached along with zinc ions. The leaching characteristics of P2O5 from the glasses are also reported. © 2003 Kluwer Academic Publishers.